2008
DOI: 10.1128/aac.00945-07
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Activities of 11 Antimicrobial Agents and Bactericidal Activities of Vancomycin and Daptomycin against Invasive Methicillin-Resistant Staphylococcus aureus Isolates Obtained from 1999 through 2006

Abstract: We assessed MICs and minimal bactericidal concentrations of vancomycin, daptomycin, and nine other antimicrobials against methicillin-resistant Staphylococcus aureus isolates obtained from 1999 through 2006. No vancomycin, daptomycin, or linezolid resistance was observed. Clindamycin, gentamicin, and ciprofloxacin resistance decreased significantly. No tolerance to vancomycin or daptomycin was observed, nor was MIC creep seen.The increasing prevalence of community-associated methicillin-resistant Staphylococcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 20 publications
2
41
1
1
Order By: Relevance
“…Steinkraus et al, using Etest, found an increase in the percentage of MRSA isolates from blood cultures between 2001 and 2005 (16). This is in contrast to reports of stable vancomycin MICs over similar periods of time as revealed by BMD (1,7,9). These studies indicate that vancomycin susceptibility results are highly dependent on methodology and perhaps isolate source.…”
Section: Discussioncontrasting
confidence: 94%
“…Steinkraus et al, using Etest, found an increase in the percentage of MRSA isolates from blood cultures between 2001 and 2005 (16). This is in contrast to reports of stable vancomycin MICs over similar periods of time as revealed by BMD (1,7,9). These studies indicate that vancomycin susceptibility results are highly dependent on methodology and perhaps isolate source.…”
Section: Discussioncontrasting
confidence: 94%
“…Several studies have reported elevated vancomycin MICs in MRSA isolates where the MICs are at the upper end of the susceptibility range (18, 27, 38, 40-43, 50, 52). However, not all medical institutions are reporting an increase in vancomycin MICs (1,11,20,33). One study measured vancomycin MICs in MRSA isolates collected from 2002 to 2006 from nine different U.S. medical centers using a reference broth microdilution assay with a broad range of precise incremental dilutions (39).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the isolates had a MIC of 1.5 g/ml, causing the Etest results to be more elevated than the results of the other two assays. Etest also measures the MIC for a larger proportion of bacteria at ϳ10 8 CFU than the broth microdilution assays at ϳ10 4 CFU, making Etest more sensitive in detecting resistant mutants and MIC increases (11,33,43).…”
Section: Figmentioning
confidence: 99%
“…The term vancomycin "MIC creep" is now frequently used (101,276,333,374). This phenomenon has been demonstrated at a number of centers in the United States over recent years by using Etest or vancomycin broth MIC (289,333,374), while at another location in the United States, no change in vancomycin MIC was detected between 1999 and 2006 (117). In France, increases in glycopeptide MICs (predominately teicoplanin) were observed over a 20-year period (276), while in Spain, the testing of over 3,000 clinical isolates by broth microdilution between 2002 and 2006 found no change in vancomycin MICs at one institution (6).…”
Section: Global Epidemiology and Associated Features Of Hvisa And Visamentioning
confidence: 99%